2006
DOI: 10.1002/cncr.22237
|View full text |Cite
|
Sign up to set email alerts
|

Thrombocytosis as a prognostic factor for survival in patients with metastatic renal cell carcinoma

Abstract: Objectives: To describe long‐term food availability and prices from 1961 to 2007 and body mass index (BMI) trends from 1980 to 2010 in Samoa, and to contextualize these trends within political, economic, cultural, behavioral, and climatic influences. Methods: National level data on food availability and pricing were obtained from the open access database FAO (http://faostat.fao.org). Data for Samoa were collected from annual food balance sheets available for the period 1961–2007. Mean BMI for Samoan men and wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
1
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 84 publications
(61 citation statements)
references
References 62 publications
3
55
1
2
Order By: Relevance
“…Brown, et al [24] reported the same relation, and so have other reports on gastric, endometrial, cervical, and metastatic renal cell carcinoma [11,14,19,30]. However, in our cohort, neither high WBC nor low hemoglobin counts were associated with poor survival.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Brown, et al [24] reported the same relation, and so have other reports on gastric, endometrial, cervical, and metastatic renal cell carcinoma [11,14,19,30]. However, in our cohort, neither high WBC nor low hemoglobin counts were associated with poor survival.…”
Section: Discussionsupporting
confidence: 85%
“…Platelets play an important role in angiogenesis and proteolysis of the basal membrane, and both situations are present in the process of tumor growth and metastatic spread [7]. Some studies have found that thrombocytosis is associated with poor survival in renal [8][9][10][11][12][13], gynecologic [14][15][16][17][18][19][20][21], and lung tumors [22,23]. Thrombocytosis has also been evaluated in pancreatic carcinoma, but the number of patients studied is small and the results are conflicting [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…1 Platelet count can be a prognostic factor in cancer, patients presenting with thrombocytosis having a poor survival in a variety of cancers including breast cancer. [2][3][4][5] Conversely, the presence of thrombocytopenia is associated with a survival benefit and decreased metastasis. [6][7][8][9] For tumors to grow beyond 1 to 2 mm 3 , they must establish their own blood supply through angiogenesis, and there is substantial evidence that angiogenesis is regulated by platelets.…”
Section: Introductionmentioning
confidence: 99%
“…Karnofsky ps, anemia, ldh elevation, and hypercalcemia are factors that have previously been reported in the mskcc criteria and that might reflect any or all of increased tumour burden, aggressive tumour biology, or paraneoplastic processes 8,19,20 . Furthermore, neutrophilia and thrombocytosis might be markers of inflammation related to the overproduction of cytokines resulting from increased tumour burden or aggressive tumour biology 21,22 . However, our study did not reveal any association between those variables and survival.…”
Section: Discussionmentioning
confidence: 99%